Synthesis of Sustainable OPC-Blended Geopolymer Concrete: Experimental and Modeling Study - Peng Zhou; Alireza Bahrami; Bin Gan; Zhou Wang (Advances in Civil Engineering)
Geopolymer concrete (GPC) has been developed using supplementary cementitious materials to reduce the carbon footprint associated with conventional concrete production. This study aimed to explore the production and simultaneous modeling of the properties of GPC using fly ash (FA) as the primary binder and ordinary Portland cement (OPC) as a partial replacement. Mechanical tests revealed that replacing FA with up to 30% OPC resulted in a 28-day compressive strength (CS) of 33.52 MPa and a flexural strength (FS) of 15.21 MPa. X-ray diffraction (XRD) analysis indicated the formation of nepheline and albite, which are associated with sodium aluminosilicate hydrate gel, a primary strength giving product in GPC. Additionally, gene expression programming (GEP), an artificial intelligence technique, was employed to predict the mechanical properties utilizing the experimental data. The prediction models demonstrated high accuracy, with a correlation coefficient greater than 0.90. The study’s results provide valuable insights into the performance of OPC-blended FA-based GPC and propose easy-to-use empirical formulations for standard mix design and proportioning of alternative blended GPC, promoting the application of sustainable concrete.